Penggunaan silase pakan lengkap berbasis batang tebu terhadap konsumsi, retensi N, estimasi síntesis protein mikroba rumen dan performans sapi PFH jantan - Artharini Irsyammawati; Siti Chuzaemi; Hartutik Hartutik (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2011)
The main objective of the research was to know the effect of silage complete feed based on sugarcane stalk to N retention, estimated microbial protein synthesis and performance of PFH steer and to find out an ideal proportion of sugarcane stalk on silage complete feed which gave the best performance of steer in economically prices. Nine of male PFH steer age 10 – 11 months were used in randomized block design (3x3) with initial body weight as covariance on total collection method. The treatment were the proportion of sugarcane stalk and concentrate on silage complete feed which made iso N/CP on 13% crude protein (SPL1 : sugarcane stalk : concentrate = 60 : 40, added with urea 1.23 % ; SPL2 : sugarcane stalk : concentrate = 50 : 50, added with urea 0.62 %; and  SPL3 : sugarcane stalk : concentrate = 40 : 60, without urea). Parameters of the research were intake, N retention, estimated microbial protein synthesis and daily weight gain. The result showed that SPL1, SPL2, SPL3 have not significant effect (P>0.05) to intake, N retention, estimated microbial protein synthesis and daily weight gain but have significant effect (P<0.05) to organic matter digestibility (OMD), and crude protein digestibility (CPD). Overall, SPL3 tends give a better effect than the other feed treatment. SPL1 was an ideal treatment for PFH steer because more economically from the price and gave performance quite similar with other treatment. Economically value of SPL1 would be higher when the price of sugarcane was less than Rp. 200.00/kg. It could be suggested to consider the particle size of SPL, ensilage process and storage method for the best result of SPL.   Keywords: sugarcane stalk, silage complete feed (SPL), intake, N retention